Drug resistance and Curli fimbrination of escherichia coli isolated from Bangladeshi patients with urinary tract infections - Mahbub, M Murshida; Azmuda, Nafisa; Maumood, Belal; Khan, Sirajul Islam; Birkeland, Nils-Kåre; Akhter, Humaira (Dhaka University Journal of Biological Sciences, 2011)
A total of 27 isolates from patients with urinary tract infection (UTI) were screened and of these 12 were found to be Escherichia coli. All the E. coli isolates were multidrug resistant. Among the antibiotics, imipenem and polymyxin B were found to be the best, while oxacillin, cefsulodine and methicillin proved to be worst in effectiveness against the studied E. coli isolates. Only 42% of the E. coli were susceptible to trimethoprim-sulfamethoxazole (TMP–SMX), the current drug of choice for treating UTI. Middle ranged plasmids were observed in the studied isolates. Five strains expressed curli fimbriae and two elaborated cellulose; two other strains produced both curli and cellulose as extracellular matrix component. Key words: Escherichia coli; Urinary tract infection; Antimicrobial resistance; Curli fimbriae DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8972 DUJBS 2011; 20(2): 123-130